Cryptococcal Meningitis in an Immunocompetent Patient with a Ventriculo-Pleural Shunt - Raynieri Fernandez; Jose Henao; Catherine Creticos (Case Reports in Infectious Diseases)
Cryptococcal meningitis is the most common form of infection caused by Cryptococcus yeast species, followed by pulmonary infection. It is an opportunistic infection seen in patients with impaired cell immunity, most frequently in HIV patients and solid organ transplant recipients; however, it can occur in patients with no apparent immunodeficiency. We describe the case of Cryptococcus neoformans meningitis in an immunocompetent patient with aseptic cerebrospinal fluid analysis which highlights the heterogeneity of this disease.